Study of Various Factors Affecting Thermal Stability of Xylanase - Suleman, Muhammad; Jabbar, Abdul; Ikram Aujla, Muhammad (Asian Journal of Chemistry, 2012)
In this work, we have studied the factors affecting the thermal stability of xylanase. Metals like (Al3+, Cu2+, Hg2+, Li+, Mn2+) with a concentration of 5 mM were applied to determine their effect on irreversible thermal stability of xylanase. Native xylanase was near about completely destroyed at 75 ºC with half life of 19.8 min. Attachment of Al3+ slightly stabilized the enzyme with half life 46.5 min at 75 ºC. Cu2+ does not stabilize or destabilize the enzyme. Attachment of Hg2+ stabilized the enzyme at 55 ºC but stability goes on decreasing with the increase in temperature. Li+ and Mn2+ stabilized the enzyme slightly with half life 82.82 and 25.9 min, respectively. Al3+ and Hg2+ were the best metals due to their stabilizing effect. These metals stabilized the enzyme at 55 ºC with 1888.3 min and 1039.0 t1/2. Thermodynamic studies also supported the Al3+ and Hg2+ for their stabilizing capabilities. DG value of native enzyme was 97 kJ/mol at 55 ºC and DH was 119.18 kJ/mol, while DG and DH with Al3+ coordination was 102.57 and 169.11 kJ/mol at 55 ºC.